Reply to comments on "Anisotropic Microwave Properties of Vertically Aligned Carbon Nanotube Arrays" - Lum, Lucas (2025)
Accurately measuring the dielectric properties of anisotropic materials is challenging due to their fragility and small size. This study addressed these issues for vertically aligned carbon nanotubes (VACNTs) by engineering them to delaminate from the substrate, retain orientation and porosity, and grow to millimeter lengths. This approach allowed for effective use of the Nicolson-Ross-Weir (NRW) method without additional techniques. While alternative methods by Susek et al. and Knisely et al. might offer higher accuracy, the proposed method is practicable with commercially available equipment, achieving reliable dielectric measurements.